First anthracological approach for the Tafí valley (Tucumán, Argentina) - Aguirre, María G.; Peña Monné, José L.; Sampietro Vattuone, María M. (Instituto de Arqueología, Facultad de Filosofía y Letras, Universidad de Buenos Aires, 2019)
This paper presents the results of the analysis of a set of anthracological remains recovered in a stratigraphic profile located in the Tafí valley (Tucumán, Argentina). We carried out the macro-remains taxonomic identification by comparing the charcoals with a reference collection of histological sections that includes specimens of the study area flora. The charcoals were examined by observing the three diagnostic sections of the stem anatomy with a binocular magnifying glass, an optical microscope with incident light, and photographs were taken with a scanning electron microscope. We identified the following taxa: Baccharis sp., Chuquiraga sp., Alnus sp. and Chusquea sp. They are part of the local flora and would have been used during human occupations corresponding to the Regional Developments period. The data generated in this study encourages the development of this line of work in the area.